Cultural Understanding in the Indonesian Translation of the Baby-Sitters Club - Aisyah, Halida (UI Scholars Hub, 2013)
This paper examines the original American edition and the Indonesian translation of two The Baby- Sitters Club novels. The researcher focuses on how culture-specific items in the novels are translated. Javier Aixelá’s classification is used to identify culture-specific items, and the translator’s method is analyzed using the notions of foreignization and domestication by Lawrence Venuti. It is found that foreignization is the translator’s tendency in translating the two novels, which indicates that the translated version of these children’s novels promote cultural understanding. This research also fills a gap in translation study as little research has been done to study the relationship between foreignization and the intended audience of the translated works.